Phytochemical Screening and Thin-layer Chromatography Fingerprint of Lagerstroemia Parviflora (Asian Journal of Pharmaceutics (AJP), 2025)
Background: The plant Lagerstroemia parviflora has been traditionally used for various medicinal applications, yet its phytochemical profile remains insufficiently explored. Investigating the secondary metabolites of this species could reveal bioactive compounds with potential pharmacological benefits. Aims: The study aims to conduct phytochemical screening and establish a thin-layer chromatography (TLC) fingerprint of L. parviflora to identify key secondary metabolites. Materials and Methods: Leaves of L. parviflora were collected, dried, and subjected to maceration extraction using chloroform, methanol, and water. Extracts were analyzed for presence of phytoconstituents using standard qualitative assays. TLC was performed on silica gel 60F254 plates, with a mobile phase of toluene: ethyl acetate: Formic acid (5:4:1). The chromatograms were visualized under normal light, short ultraviolet (UV) (254 nm), and long UV (365 nm), and retention factor (Rf) values were recorded. Results: Phytochemical screening of L. parviflora revealed flavonoids in chloroform and aqueous extracts; diterpenes, phenols, proteins, and carbohydrates in the methanolic extract; saponins and tannins in the aqueous extract; and sterols in the chloroform extract, while alkaloids were absent. TLC analysis showed multiple flavonoid-related bands, with the chloroform extract exhibiting six spots under UV light (Rf = 0.4–1.0), the methanolic extract showing up to 7 spots (Rf = 0.12–1.0), and the aqueous extract displaying fewer bands. Notably, several spots near Rf = 0.64 align with quercetin, indicating flavonoid-rich profiles with potential antioxidant and therapeutic relevance. Conclusion: The findings suggest that L. parviflora possesses significant bioactive compounds, particularly flavonoids and phenolics, which could be explored for antioxidant and therapeutic applications. Further investigation into isolation, purification, and bioactivity assays of identified compounds is needed to establish their pharmacological potential.